Second nature : economic origin of human evolution - Ofek, Haim, 1936- (Cambridge University Press, 2001)
Was exchange an early agent of human evolution or is it merely a de novo artifact of modern civilisation? Here, Haim Ofek explores the impact of market forces on human evolution, from the feed-as-you-go strategy typical of primates to the development of agriculture and the domestication of fire.